Future pandemics and vaccination: Public opinion and attitudes across three European countries. Issue 6 (3rd February 2016) - Determann, Domino; de Bekker-Grob, Esther W.; French, Jeff; Voeten, Helene A.; Richardus, Jan Hendrik; Das, Enny; Korfage, Ida J.
Highlights: We explored pandemic vaccination opinions and attitudes across 3 European countries. Participants overall expressed similar considerations, though differences stand out. Adherence to social norms and rules was most common in Swedish participants. Polish participants trusted health professionals and the national government least. Abstract: Background: Understanding public opinion and attitudes regarding vaccination is crucial for successful outbreak management and effective communication at the European level. Methods: We explored national differences by conducting focus group discussions in The Netherlands, Poland and Sweden. Discussions were structured using concepts from behavioural models. Results: Thematic analysis revealed that participants would base their vaccination decision on trade-offs between perceived benefits and barriers of the vaccine also taking into account the seriousness of the new outbreak. Except for those having chronic diseases, participants expected a low infection risk, resulting in a low willingness to get vaccinated. Information about the health status of cases was considered important since this might change perceived susceptibility. Participants displayed concerns about vaccine safety due to the limited available time to produce and test vaccines in the acute situation of a new pandemic. Swedish participants mentioned their tendency of doing the right thing and following the rules, as well as to get vaccinated because of solidarity with other citizens and social influences. This appeared much less prominent for the Dutch and Polish participants. However, Swedish participants indicated that their negative experiences during the Influenza A/H1N1 2009 pandemic decreases their acceptance of future vaccinations. Polish participants lacked trust in their national (public) health system and government, and were therefore sceptical about the availability and quality of vaccines in Poland. Conclusions: Although participants overall expressed similar considerations, important differences between countries stand out, such as previous vaccination experiences, the degree of adherence to social norms, and the degree of trust in health authorities.